Cropping system sustainability tool 'CROSST' is an Excel-based tool assessing both agro-environmental and socio-economic impacts of Green Manure Cover Crop (GMCC) technologies - CGIAR Research Program on Water, Land and Ecosystems (2019)
The tool quantifies gross economic margin, productivity (yield), soil health (N and P balances, soil structure, and soil organic carbon), required labor hours, and the trade-offs between these indicators. The tool was pilot-tested in Benin and Kenya under the BMZ-GIZ program on ‘Soil Protection and Rehabilitation for Food Security.’